2014
DOI: 10.1038/nn.3813
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing an emotional valence map in the limbic forebrain by TAI-FISH

Abstract: A fundamental problem in neuroscience is how emotional valences are represented in the brain. We know little about how appetitive and aversive systems interact and the extent to which information regarding these two opposite values segregate and converge. Here we used a new method, tyramide-amplified immunohistochemistry-fluorescence in situ hybridization, to simultaneously visualize the neural correlates of two stimuli of contrasting emotional valence across the limbic forebrain at single-cell resolution. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
112
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 48 publications
8
112
1
1
Order By: Relevance
“…In rodents, optogenetic stimulation of mPFC neurons, mPFC to raphe projections, and VTA dopaminergic neurons achieved a rapid reversal of stress-induced maladaptive behaviors 4,11,12 .. We speculate that our acute behavioral changes reflect the degree to which directly stimulating positive memory engram-bearing cells might bypass the plasticity that normally takes antidepressants weeks or months to achieve, thereby temporarily suppressing the depression-like state. In support, we observed that the effects of optically stimulating a positive memory are contingent on active glutamatergic projections from the amygdala to the NAcc in real-time, as well as intra-NAcc dopamine activity 19 . Our data dovetail with this circuit's proposed role of relaying BLA stimulus-reward associations to a ventral striatal motor-limbic interface.…”
supporting
confidence: 67%
See 4 more Smart Citations
“…In rodents, optogenetic stimulation of mPFC neurons, mPFC to raphe projections, and VTA dopaminergic neurons achieved a rapid reversal of stress-induced maladaptive behaviors 4,11,12 .. We speculate that our acute behavioral changes reflect the degree to which directly stimulating positive memory engram-bearing cells might bypass the plasticity that normally takes antidepressants weeks or months to achieve, thereby temporarily suppressing the depression-like state. In support, we observed that the effects of optically stimulating a positive memory are contingent on active glutamatergic projections from the amygdala to the NAcc in real-time, as well as intra-NAcc dopamine activity 19 . Our data dovetail with this circuit's proposed role of relaying BLA stimulus-reward associations to a ventral striatal motor-limbic interface.…”
supporting
confidence: 67%
“…3c) of BLA neurons and simultaneous activation of ChR2-mCherry-positive DG cells, respectively, in stressed mice. At the neuronal level, light-induced reactivation of DG cells previously activated by a positive experience also reactivated BLA 8 and NAcc 19 , but not mPFC, cells (i.e. endogenous c-Fos + cells, red) previously activated by the same positive experience (i.e.…”
mentioning
confidence: 93%
See 3 more Smart Citations